Indonesia Economic Quarterly, March 2015 : High Expectations - World Bank (Washington, DC, 2015)
Effective January 1, 2015, Indonesia’s new government took the decisive step of implementing a new fuel pricing system, dramatically reducing gasoline and diesel subsidy costs. This paved the way for the government’s first budget, passed in February, to shift spending towards development priorities, especially infrastructure, the allocation for which is double the 2014 outturn. Successful implementation of the bold vision of the budget, however, will require overcoming administrative constraints to spending and dramatically lifting revenue collection performance. Achieving this, and having the benefits flow through into faster economic growth and poverty reduction, is likely to take time, especially with the pace of sustainable economic growth having slowed, due partly to lower commodity prices. Beyond the fiscal sector, reforms taken in the first months of the government’s term in key areas such as investment licensing also face complex challenges to make operational. The government has signaled its strong reform intentions, and raised expectations. Early progress will now need to be consolidated by effectively implementing major reforms and the budget posture, against a still-challenging global economic backdrop for Indonesia.